Role of Complement in Enterohemorrhagic Escherichia coli–Induced Hemolytic Uremic Syndrome - Orth-Höller, Dorothea; Würzner, Reinhard (Seminars in Thrombosis and Hemostasis, 2014)
Hemolytic uremic syndrome (HUS), the most common cause of acute renal failure in childhood, is mainly caused by infection with Shiga toxin (Stx)-producing enterohemorrhagic Escherichia coli (EHEC). Besides its cytotoxic activity, Stx has been shown to interact with the complement system. Complement breakdown products have been found in serum of HUS patients suggesting complement activation and in vitro studies have demonstrated that Stx2 directly activates complement leading to formation of terminal complement complex. Furthermore, Stx2 has been found to bind to factor H (FH) resulting in a reduced cofactor activity on the cell surface. Binding of Stx2 has also been shown for other members of the FH family, namely FH-like protein 1 and FH-related protein 1. Both proteins also compete with FH for Stx binding, so that in the presence of FHR-1 less FH is bound to Stx and therefore more is available for endothelial cell protection. In addition, Stx2 has been demonstrated to downregulate the membrane-bound regulator CD59 on the surface of glomerular endothelial and tubulus epithelial cells on protein and at the mRNA level. In conclusion, Stx modulates complement regulator proteins leading to an impaired control and thus to enhanced complement activation. Its implication in the pathogenesis of EHEC-induced HUS in vivo and whether complement blockage might be a therapeutic option still has to be elucidated.
Keywords: hemolytic uremic syndrome; Shiga toxin; complement; factor H family proteins; membrane-bound complement regulators